2021
DOI: 10.3389/fmed.2021.604085
|View full text |Cite
|
Sign up to set email alerts
|

Graft Failure in Patients With Hematological Malignancies: A Successful Salvage With a Second Transplantation From a Different Haploidentical Donor

Abstract: Graft failure (GF) is a fatal complication of allogeneic stem cell transplantation, especially after haploidentical transplantation. The mortality of GF is nearly 100% without an effective salvage method. A second transplantation is usually necessary to save the patient's life. However, there is no standardized regimen, and the outcome is usually disappointing. We report on a prospective single-center study using a reduced-intensity conditioning regimen with different haploidentical donors (HIDs). Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Graft failure and disease relapse are the main reasons that lead to retransplantation mentioned in a study (16) . Factors associated with graft failure include HLA incompatibility, underlying disease, type of conditioning regimen, source of CPH employed, low HPC dose, ex vivo T cell depletion, major ABO incompatibility, grafts from female donors to male recipients and disease status at the transplantation time, infection or sepsis and nonadherence to drug therapy with ursodeoxycholic acid and immunosuppressants in the post-HSCT period (17) . The latter two mentioned were pointed out by the results of this research as factors which increase the chances of retransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Graft failure and disease relapse are the main reasons that lead to retransplantation mentioned in a study (16) . Factors associated with graft failure include HLA incompatibility, underlying disease, type of conditioning regimen, source of CPH employed, low HPC dose, ex vivo T cell depletion, major ABO incompatibility, grafts from female donors to male recipients and disease status at the transplantation time, infection or sepsis and nonadherence to drug therapy with ursodeoxycholic acid and immunosuppressants in the post-HSCT period (17) . The latter two mentioned were pointed out by the results of this research as factors which increase the chances of retransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Graft failure and disease relapse are the main reasons that lead to retransplantation mentioned in a study 16 . Factors associated with graft failure include HLA incompatibility, underlying disease, type of conditioning regimen, source of CPH employed, low HPC dose, ex vivo T cell depletion, major ABO incompatibility, grafts from female donors to male recipients and disease status at the transplantation time, infection or sepsis and non-adherence to drug therapy with ursodeoxycholic acid and immunosuppressants in the post-HSCT period 17 . The latter two mentioned were pointed out by the results of this research as factors which increase the chances of retransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest retrospective study published so far on alternative salvage transplantations in the context of graft failure (699 patients between 2007 and 2016), Harada et al 30 found a 45.1% TRM in haplo‐ and 49.8% in CB‐HSCT. A prospective clinical trial led by the Peking University Institute of Hematology 31 reported an experience of salvage haplo‐HSCT using a fludarabine/cyclophosphamide regimen with a promising 56.6% 1‐year OS and 23.1% 1‐year TRM. Finally, development of non‐transplant treatments (TKI in CML, anti‐CD19 therapies in ALL, etc.)…”
Section: Discussionmentioning
confidence: 99%